Fermented palm kernel waste with different sugars as substrate for black soldier fly larvae - R.A. Nugroho; R. Aryani; E.H. Hardi; H. Manurung; R. Rudianto; W.N. Jati (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The palm industry generates several waste products. Some of this waste, such as palm kernel meal, has not been fully optimized for processing. Therefore, this study sought to determine whether fermented palm kernel meal with various types of sugar (fructose, glucose, maltose, and sucrose) added could be utilized as a substrate for black soldier fly larvae.METHODS: This study investigated the use of fermented palm kernel meal with various types of sugar added at a proportion of five per cent as a substrate for black soldier fly larvae. Fermented palm kernel meal without added sugar was used as a control substrate. Seven-day-old larvae were fed fermented palm kernel meal as an experimental substrate for 22 days and harvested on the final day, when their weight and length were measured and they were processed into meal and oil to evaluate their nutritional composition. FINDINGS: The addition of sugars to fermented palm kernel meal made no significant difference to the final weight or crude fat value of the larvae, but improved crude protein. The addition of glucose significantly increased the length of the larvae and increased their lauric acid value. However, glucose-added fermented palm kernel meal significantly reduced the relative percentage of total unsaturated fatty acids and the quantities of linolelaidic, a-linolenic, and nervonic acid compared to the larvae fed on substrates with other added sugars. Meanwhile, fructose-added substrate resulted in significantly higher crude protein and moisture values, but significantly lower ash and carbohydrate values than those of other groups. Sucrose-added substrate resulted in a considerable improvement in ash content; magnesium; the relative percentage of total unsaturated fatty acids; arachidic, erucic, and docosadienoic acid; phosphorus; sodium; and iron values in the larvae. The larvae grown in the substrate with added maltose had a significantly higher accumulation of phosphorus, sodium, and iron, but showed significantly lower palmitoleic acid than other larvae groups. Calcium and potassium were accumulated better in the larvae grown on fermented palm kernel meal with added either glucose, maltose, or sucrose than other substrates.CONCLUSION: of the various waste products generated by the palm industry, some, including palm kernel meal, have not yet been entirely processed. This study’s findings offer insights into managing the fermented palm kernel meal, which can be converted into valuable biomass with black soldier fly larvae, making the waste more sustainable and rich in nutrients. The addition of various sugars to fermented palm kernel meal improved the growth and nutritional value of the black soldier fly larvae. These results may help in building a process for the effective treatment of palm kernel meal for black soldier fly larvae production, which could further develop the feed industry and manage palm industry waste effectively by generating high protein meal as a step in creating a circular bioeconomy.